2015
DOI: 10.1016/j.seizure.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Can the adverse effects of antiepileptic drugs be detected in saccadic eye movements?

Abstract: The total latency and accuracy of video-based electro-oculography may be screened to identify patients with a high risk of adverse effects with antiepileptic-drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The effects of drugs on EM have been studied for a long time (Wise, 1984 ). One reason for this is they inform us about drug effects on the central nervous system (Park et al, 2015 ). Psychotropic drugs can alter the basic EM but also have an impact on oculomotor performances in emotional information processing (Sweeney et al, 1994 ; Reilly et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of drugs on EM have been studied for a long time (Wise, 1984 ). One reason for this is they inform us about drug effects on the central nervous system (Park et al, 2015 ). Psychotropic drugs can alter the basic EM but also have an impact on oculomotor performances in emotional information processing (Sweeney et al, 1994 ; Reilly et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants with corrected vision were asked to remove their glasses and wear COMO SPORT L glasses with lenses adjusted to their visual acuity for the duration of the experiment. Participants were excluded from the study if they had a history of seizures, traumatic brain injury, psychiatric or neurodevelopmental conditions other than autism (not including ADHD or anxiety), or if they were taking any antiepileptic or anticonvulsant medication, as these can impact eye movements (Aschoff, 1968;Cohen et al, 1985;Tedeschi et al, 1989;Remler et al, 1990;Zaccara et al, 1992;Goldman and Schultz-Ross, 1993;Hilton et al, 2004;Lo et al, 2008;Reilly et al, 2008;Park et al, 2015;Lunn et al, 2016). The current study was approved by the Institutional Review Boards (IRB) of the University of Rochester Medical Center and of the Albert Einstein College of Medicine.…”
Section: Participants and Phenotypic Assessmentsmentioning
confidence: 99%
“…10 The movements of the left eye were recorded using a high-resolution infrared scleral reflectance technique (resolution 320 × 240 pixels, sampling rate 60 Hz, SLVNG; SLMED Inc., Seoul, Korea). The visual stimulus was a white square target on a dark-blue background.…”
Section: Video-oculographymentioning
confidence: 99%
“…9 Additionally, we recently demonstrated that saccadic eye movements using video-oculography (VOG) can be screened to identify patients with a high risk of adverse reactions to AEDs. 10 However, no study has investigated whether eye movements could reflect the efficacy of AEDs in patients with epilepsy. The aim of this study was to determine whether the efficacy of AEDs could be assessed with eye movements using VOG.…”
Section: Introductionmentioning
confidence: 99%